2011
DOI: 10.1111/j.1349-7006.2011.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion front‐specific expression and prognostic significance of microRNA in colorectal liver metastases

Abstract: The tumor edge of colorectal cancer and its adjacent peritumoral tissue is characterized by an invasion front-specific expression of genes that contribute to angiogenesis or epithelial-to-mesenchymal transition. Dysregulation of these genes has a strong impact on the invasion behavior of tumor cells. However, the invasion front-specific expression of microRNA (miRNA) still remains unclear. Therefore, the aim of the present study was to investigate miRNA expression patterns at the invasion front of colorectal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…Previous studies demonstrated that miR-19b overexpression was related to 5-FU resistance in colon cancer cells (Kurokawa et al 2012) and was an adverse prognostic marker of recurrence and overall survival in patients with colorectal cancer (Kahlert et al 2011). Aberrant expression of miR-146a was correlated with complete remission rate, higher overall response rate and longer progression-free survival time in patients with diffuse large B-cell lymphoma (Zhong et al 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies demonstrated that miR-19b overexpression was related to 5-FU resistance in colon cancer cells (Kurokawa et al 2012) and was an adverse prognostic marker of recurrence and overall survival in patients with colorectal cancer (Kahlert et al 2011). Aberrant expression of miR-146a was correlated with complete remission rate, higher overall response rate and longer progression-free survival time in patients with diffuse large B-cell lymphoma (Zhong et al 2012).…”
Section: Discussionmentioning
confidence: 89%
“…The miR17-92 cluster has been designated oncomir-1 (31), and can promote proliferation and angiogenesis, inhibit differentiation, and sustain cell survival (29,30). Elevated miR17-92 levels have been associated with invasion and metastasis of colorectal cancer cells (32), and poorer survival (33). miR19a and miR19b in particular are key oncogenic determinants (29,30), and both were significantly elevated with the HRM diet compared with the entry diet.…”
Section: Discussionmentioning
confidence: 99%
“…6) Therefore, let-7b may play an important role in CRC metastasis. The intracellular expression levels of let-7c and let-7g have been associated with the metastasis of colorectal and breast cancers, respectively.…”
Section: Discussionmentioning
confidence: 99%